2018
DOI: 10.1002/adem.201701137
|View full text |Cite
|
Sign up to set email alerts
|

Superior Cryogenic Tensile Strength and Ductility of In Situ Al–Cu Matrix Composite Reinforced with 0.3 wt% Nano‐Sized TiCp

Abstract: In the present work, the tensile properties at 77 K of the 0.3 wt% nano‐sized TiCp/Al–Cu composite is investigated to explore its potential application at cryogenic temperature. The TiCp/Al–Cu composite exhibits superior ultimate tensile strength (620 MPa), yield strength (531 MPa), and fracture strain (7.2%) at 77 K. The addition of TiCp leads to the refinement of θ′ precipitates and enhanced dislocation strengthening effect, contributing to the improved tensile strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…This phenomenon is very rare for general materials, which would experience a reduction in tensile properties as the temperature increases due to the lower lattice friction for crystals or higher chain mobility for polymers. [38,39] For practical application, the mechanical performance of a phase change film is crucial. The flexible and robust features of OANF-PNIPAM films guarantee that they can work properly under mechanical deformations or external forces.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is very rare for general materials, which would experience a reduction in tensile properties as the temperature increases due to the lower lattice friction for crystals or higher chain mobility for polymers. [38,39] For practical application, the mechanical performance of a phase change film is crucial. The flexible and robust features of OANF-PNIPAM films guarantee that they can work properly under mechanical deformations or external forces.…”
Section: Resultsmentioning
confidence: 99%
“…The low-temperature yield strength and elongation of the alloy in this study are compared with other FCC structural alloys, as shown in Figure 9A. Clearly, the present HEA has better low-temperature mechanical properties than those of other alloys, for example, Al alloys [30] , high Mn steels [31] , Ni-based steels [32,33] , transformation-induced plasticity steels [34] and other HEAs [4,[23][24][25][35][36][37][38][39][40][41][42][43] . It is particularly obvious that the yield strength and UTS are the highest, with values of 1080 and 1150 MPa, annealed at 600 °C, respectively, with a loss of ductility.…”
Section: Mechanical Properties Of Heamentioning
confidence: 88%
“…Thus, the effect of dislocation strengthening was further enhanced in the cryogenic environment. [ 21 ] Dislocation pile‐ups against grain boundaries and entangles in the grains, as shown in Figure 8d. The larger the density of the dislocations were at the grain boundary, the greater contribution they had to the Hall–Petch effect.…”
Section: Discussionmentioning
confidence: 99%